The Effect of the LOC-R Learning Model on Fifth-Grade Students’ Critical Thinking Skills in Mathematics Learning - Mardiana, Tria; Muzayyanah, Arifah (EDUPEDIA Publisher, 2026)
Purpose – This study aims to examine the effect of the LOC-R (Literacy, Orientation, Collaboration, and Reflection) learning model on fifth-grade students’ critical thinking skills in mathematics, addressing the need for instructional approaches that move beyond procedural learning toward higher-order thinking. Methodology – A quasi-experimental method with a one-group pretest–posttest design was employed. The participants consisted of 20 fifth-grade students from SD Negeri Sosrowijayan. The intervention involved the implementation of the LOC-R learning model in mathematics instruction. Data were collected using a critical thinking skills questionnaire developed based on eight critical thinking indicators. Data analysis included descriptive statistics, normalized gain (N-gain), and a paired-sample t-test to determine the significance of the observed differences. Findings – The results revealed a substantial improvement in students’ critical thinking skills following the implementation of the LOC-R learning model. The mean score increased from 65 on the pretest to 85 on the posttest, with an N-gain value of 0.67, indicating a moderate-to-high level of improvement. The paired-samples t-test showed a statistically significant difference between pretest and posttest scores (p < 0.05), confirming the intervention's effectiveness. Novelty – This study provides experimental-based empirical evidence on the effectiveness of the LOC-R learning model, which has predominantly been examined through descriptive approaches in previous research. Significance – The findings offer practical implications for elementary school teachers, curriculum developers, and education researchers seeking effective instructional models to enhance students’ critical thinking skills in mathematics learning.